2021
DOI: 10.3389/fimmu.2021.710121
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin Glycoprotein Ligand 1: A Potential HIV-1 Therapeutic Target

Abstract: Antiretroviral therapy (ART), which is a life-long therapeutic option, remains the only currently effective clinical method to treat HIV-1 infection. However, ART may be toxic to vital organs including the liver, brain, heart, and kidneys, and may result in systemic complications. In this context, to consider HIV-1 restriction factors from the innate immune system to explore novel HIV therapeutics is likely to be a promising investigative strategy. In light of this, P-selectin glycoprotein ligand 1 (PSGL-1) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 132 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…For now, it is known that IFN-α treatment simultaneously enhances (i) cytokine secretion, polyfunctionality, degranulation, cytotoxic potential, and the suppressive capacity of NK cells, and (ii) the suppressive capacity of CD8+ T cells [148] . Moreover, supplementation with IFN-γ is likely to trigger P-selectin glycoprotein ligand-1 expression, and thus enhance the recruitment of effector cells, inhibit virion infectivity, and suppress HIV replication, as explored in detail in a recent review by our group [149] …”
Section: Challenges Of the Sech Strategymentioning
confidence: 95%
See 1 more Smart Citation
“…For now, it is known that IFN-α treatment simultaneously enhances (i) cytokine secretion, polyfunctionality, degranulation, cytotoxic potential, and the suppressive capacity of NK cells, and (ii) the suppressive capacity of CD8+ T cells [148] . Moreover, supplementation with IFN-γ is likely to trigger P-selectin glycoprotein ligand-1 expression, and thus enhance the recruitment of effector cells, inhibit virion infectivity, and suppress HIV replication, as explored in detail in a recent review by our group [149] …”
Section: Challenges Of the Sech Strategymentioning
confidence: 95%
“…[148] Moreover, supplementation with IFN-g is likely to trigger P-selectin glycoprotein ligand-1 expression, and thus enhance the recruitment of effector cells, inhibit virion infectivity, and suppress HIV replication, as explored in detail in a recent review by our group. [149]…”
Section: Challenges From Immune System Effector Cellsmentioning
confidence: 99%
“…To achieve the infiltration, the binding of sLeX on the leukocytes to the E-and P-selectins on the endothelial surface at the inflammation area is required [56]. These two selectins probably function similarly in regulating the infiltration; sLeX capped O-glycans on P-selectin glycoprotein ligand 1 (PSGL-1) at the leukocyte surface binds to the two selectins and thus makes leukocytes roll following the blood flow direction [57][58][59][60], without the binding of PSGL-1 to the two selectins, leukocytes could not initiate rolling on the endothelial surface [27,61,62]. Overcoming the hydrodynamic force of the blood flow is an essential aim of selectin-sLeX binding for leukocyte rolling, Zhang et al [63] identified the molecular determinants within sLeX that contributes to the binding using single-molecule dynamic force spectroscopy; two determinants in sLeX are required for the selectin binding, which is the Fuc and the terminal Neu5Ac.…”
Section: In Immunitymentioning
confidence: 99%
“…Despite extensive global research and study (1)(2)(3), a cure for HIV infection has, thus far, proven elusive. Recently, our research group has proposed novel potential therapeutic options for HIV infection (4,5) which, we believe, could inspire future clinical trials into curative therapeutic options for HIV. Our first proposition concerns the promotion of P-selectin glycoprotein ligand 1 (PSGL-1), an important receptor from innate immunity, which (i) induces the production of membrane defective virions that are unable to attach to or infect new target cells, and (ii) blocks the HIV reverse transcription process.…”
Section: Introductionmentioning
confidence: 99%